Visible and Invisible : The Wonders of Light Phenomena - Bisi, Olmes (Astronomers' Universe,, 2015)
Light phenomena have intrigued humankind since prehistory. Think of the rainbow, a sunset on the sea, a game of shadows. Humans have always used light for their own needs, from cooking food to illuminating a room. However, light is not only limited to what we can see with our eyes. The invisible part of the electromagnetic spectrum is broad and dynamic. This book outlines the mysteries and wonders of electromagnetism, heat, and light. It also covers the history of our scientific understanding of light. The dark as well as the bright sides of light are fully explored in these pages, from their impact on our world to their use in cutting-edge technologies in a variety of fields. Numerous full-color images and drawings complement the text, and light phenomena are explained in a simple and engaging way.